Effects of biological treatments on production and quality parameters of soybean (Glycine max L. Merrill) (Bangladesh Journal of Botany, 2025)
Innovative approaches such as seed treatment with lactic acid bacteria (LAB), mycoparasitic fungi (MPF), and entomopathogenic fungi (EPF) can improve yield and quality. A plot experiment with the variety Abaca was conducted on organically certified plots at two climatically distinct sites in the Czech Republic. In the early growth stages, MPF and LAB treatments showed slight improvements in root length, weight, and plant dry matter. Other parameters, including plant height before harvest, thousand-grain weight, and yield, showed a positive but statistically inconclusive effect. Regarding quality, a beneficial impact of MPF and LAB on protein content in seeds was recorded. Starch and oil contents were unaffected. The differences were relatively small, suggesting that biological seed treatments support soybean yield and quality, particularly when combined with other agrotechnical measures.Bangladesh J. Bot. 54(3): 687-693, 2025 (September) Special